Building Memories The Neolithic Cotswold Long Barrow at Ascott-under-Wychwood, Oxfordshire - Whittle, Alasdair (Historic England, 2006)
It is just over forty years since the start of the excavations of the Ascott-under-Wychwood long barrow (1965-69) under the direction of Don Benson. The excavations belonged to the latter part of a great period of barrow digging in southern Britain, which was ending just as, by striking contrast, intensified investigation and fieldwork at causewayed enclosures were beginning. Although a long gap has passed since the excavations took place, they have nonetheless produced a rich and important set of results, and the analysis has been enhanced by more recent techniques. The site now joins Burn Ground and Hazleton North as one of only three Cotswold long barrows or cairns to have been more or less fully excavated. The authors of this report not only document the finds and research, but also address wider questions of how the early Neolithic inhabitants viewed their society through the barrow, and how the development of the site reflected memory and interaction with a changing world.